EVALUATION OF BODY FLEXIBILITY AND FUNCTIONAL INDEPENDENCE IN INDIVIDUALS WITH SPINAL CORD INJURY: BASKETBALL ON WHEELS (Fiep Bulletin - online, 2012)
Introduction: Patients with spinal cord injury of different etiologies may have functional limitations and difficulties in carrying out their daily activities due to low trunk control and flexibility, immobility and psychological changes as a result of acceptance and reintegration. The adapted sports physical therapy along with acts intended to reduce or mitigate these limitations, the most redeeming the independence of these patients. The adapted sports shows high rates of acceptance, pleasurable activities become practitioners and to improve self-esteem, the instinct of competition, social interaction and functional capacity of these individuals. Objective: To evaluate the flexibility of the trunk and functional independence in patients with spinal cord injury before and after basketball practice on wheels. Methodology: The study consisted of 8 male patients diagnosed with neurological complete and incomplete spinal cord injury. To assess the functionality of the scale was used functional independence measure (FIM) validated in Brazil in 2001. To assess trunk flexibility, we used an inclinometer that measures brand Sany active range of motion of the patient. Results: Through this study we analyzed the results by using SPSS 15.0, and could be seen that the application of the scale (FIM) were not seen significant results only in the items: food, personal hygiene, control of urine control feces, comprehension and expression, the other items, were significant when subjected to the Wilcoxon test (
Keywords: Basketball adapted; functional independence; flexibility.